Investigating the Impact of Diet, Physical Activity, and Lifestyle on MASLD Risk in Adults in Qatar - Eljazzar, Sereen; Mezhoud, Souraia; Tayyem, Reema (Bangladesh Journal of Medical Science, 2025)
Background Metabolic dysfunction-associated steatotic liver disease (MASLD) outcomes are significantly influenced by dietary habits, lifestyle behaviors, and physical activity. Aim This cross-sectional study evaluated the relationship between dietary habits, dietary diversity, physical activity levels, lifestyle behaviors, and their associations with MASLD indicators in Arab adults in Qatar. Methods A descriptive cross-sectional study was conducted with 94 participants. Data on demographics, health status, lifestyle, and dietary habits were collected using the Participant’s Personal and Dietary Habits Information Questionnaire. Dietary diversity was assessed using the Food Groups Consumption (FGC) score. Physical activity and sleep were evaluated via the Seven-Day Physical Activity Recall form. Descriptive statistics and linear regression were employed to examine associations between MASLD indicators (BMI, lipid profile, liver enzymes, and glucose levels) and dietary habits. Results BMI was associated with snacking (Ptrend=0.049), while the timing of the first meal correlated with total cholesterol (Ptrend=0.045), low-density lipoprotein (Ptrend=0.047), and fasting blood sugar (Ptrend=0.026). An inverse association was detected between the timing of the last meal and high-density lipoproteins (Ptrend=0.007). Triglyceride levels were associated with both skipped meals (Ptrend=0.010) and eating out (Ptrend=0.002). All participants had adequate dietary diversity (FGC score of 101.9), with no differences between food group intakes except for males consuming more fruit than females (P=0.042). Physical activity analysis revealed that female participants had significantly higher levels of moderateintensity exercise during both weekdays (P=0.014) and weekends (P=0.026), as well as more total MET minutes of moderate-intensity physical activity compared to males (P=0.011). Conclusion Dietary habits, such as snacking, meal skipping, meal timing, and eating out, were associated with MASLD-related anthropometric and biochemical indicators. This study provides valuable insights into dietary and lifestyle factors contributing to MASLD and highlights the need for further research with more robust study designs in Qatar. BJMS, Vol. 24 No. 03 July’25 Page : 837-852